Renewable energy : physics, engineering, environmental impacts, economics and planning - Sørensen, Bent (Academic Press is an imprint of Elsevier, 2017)
This book covers the basic scientific principles behind all major renewable energy resources, such as solar, wind, and biomass. It explores how these raw renewable sources can be converted into useful forms, transmitted into the grid, and stored for future utilization as well as the aspects of energy planning, environmental impacts, and socio-economic issues on regional and global levels.